Prevalence and Management of Pediatric Urinary Tract Infections in Wasit Governorate, Iraq (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Urinary tract infections (UTIs) represent a significant health concern among pediatric populations, contributing to considerable morbidity in both boys and girls. This study aimed to isolate and identify the most common bacterial pathogens associated with UTIs in children in the city of Kut, Iraq. A total of 105 urine samples were collected from pediatric patients aged between 4 days and 10 years, who were admitted to Al-Zahra General Hospital and Kut Maternity and Pediatric Hospital, during the period from October 2023 to February 2024. Out of the total samples, 45 (38.09%) were confirmed as positive bacterial isolates, including Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis. The results demonstrated a higher prevalence of infection among females (55.23%) compared to males (44.79%), and younger age groups showed higher infection rates than older children. Antibiotic therapy was the most commonly prescribed treatment (95%), with amoxicillin and trimethoprim being the most frequently administered. Non-steroidal anti-inflammatory drugs (NSAIDs), such as paracetamol, were used in 57% of cases, while surgical intervention, particularly circumcision, was considered the most effective treatment in 8% of cases.